Solution Focused Brief Therapy: A Systematic Review and Meta‐Summary of Process Research. (19th October 2016) - Franklin, Cynthia; Zhang, Anao; Froerer, Adam; Johnson, Shannon
Abstract : This article presents a systematic review of the process research on solution‐focused brief therapy (SFBT). We searched published and unpublished studies in English across five databases, five major journals, two book chapters, and four websites to locate studies that investigate why and how SFBT works. Thirty‐three studies that used various research methods were located and included for further analysis using a meta‐summary approach. The findings supported the significance of the co‐construction process within SFBT and the effects of specific types of SFBT techniques. The most empirical support was found for the strength‐oriented techniques in comparison to the other techniques and for the co‐construction of meaning. Current studies require replications with larger samples and experimental designs that study SFBT process in relationship to outcomes.